Feed these people : slam-dunk recipes for your crew - Hatmaker, Jen (Harvest, an imprint of William Morrow, 2022)
"With five children and a close-knit community of family and friends, bestselling author, podcaster, and inspirational speaker Jen Hatmaker has been sharing her love of cooking and food with her fans for years. Now she's compiled all her favorite sure-thing recipes into one personal and highly entertaining cookbook, including chapters like Food for Breakfast (or brunch so you can drink), Food for Your Picky Spouse or Spawn, and Food for When You Have No More Damns to Give. This is real food for real people... Paired with vibrant photography that's as bold and lively as Jen herself, all recipes are sure to please, written for ordinary home cooks, and infused with personal notes, asides, and stories in her candid and irreverent style." -- Amazon.